Comprehensive Analysis of the Association Between the rs1138272 Polymorphism of the GSTP1 Gene and Cancer Susceptibility - Ding, Fei; Li, Jin-Ping; Zhang, Yong; Qi, Guang-Hui; Song, Zhi-Chao; Yu, Yong-Hua (Frontiers in Physiology, 2019)
Background: We obtained conflicting results regarding the relationship between the genetic role of the rs1138272 C/T polymorphism of the GSTP1 (Glutathione S-Transferase pi) gene and the risk of various cancers. Method: Using the presently available data, a meta-analysis was conducted to comprehensively evaluate the genetic relationship between the GSTP1 rs1138272 polymorphism and cancer susceptibility. Result: A total of 43 studies including 15,688 cases and 17,143 controls were recruited into our quantitative synthesis. In the overall population, we observed an increased risk of overall cancer cases, compared with unrelated controls, in the genetic models of allele T vs. allele C (P-association =0.007, OR=1.17), carrier T vs. carrier C (P-association =0.035, OR=1.11), TT vs. CC (P-association =0.002, OR=1.45), TT vs. CC+CT (P-association =0.009, OR=1.42), and CT+TT vs. CC (P-association =0.027, OR=1.13). We detected similar positive results within the Asian population. Additionally, there was a significant increase in the incidence of cancer for Africans under all genetic models (all P-association<0.05, OR>1). When targeting the Caucasian population, we detected a positive association with the TT vs. CC and TT vs. CC+CT models in the “Colorectal cancer” (P-association <0.05, OR<1) and “Head and neck cancer” (P-association <0.05, OR>1) subgroups. For the “Lung cancer” subgroup, we observed a slightly increased risk in Caucasians under the models of allele T vs. allele C, carrier T vs. carrier C, CT vs. CC, and CT+TT vs. CC (P-association<0.05, OR>1). Conclusion: The TT genotype of the GSTP1 rs1138272 polymorphism is likely related to the susceptibility to overall cancer in the Asian and African populations and, specifically, “Colorectal” and “Head and neck” cancers in the Caucasian population. In addition, the CT genotype of the GSTP1 rs1138272 polymorphism may be linked to the risk of lung cancer in Caucasians. Additional evidence is required to confirm this conclusion.